Kosowo jako kolebka i skarbiec serbskiej duchowości w historii oraz współczesnej świadomości wschodnich Słowian - Czarota, Iwan A. (Elpis, 2015)
In this paper, the author reveals and analyses the presence of remembrance of Kosovo and Metohija – the cradle of Serbian statehood, the seat of the Serbian Orthodox Church and a treasury of Serbian culture – in the historical and current awareness of Eastern Slavs. Kosovo and Metohija is analysed as the main topic of Serbology in Eastern Slavic literatures. The term “Eastern Slavs” has concrete historical meanings:1) the Russian people, that is, its ethno-spiritualcultural community in the past; 2) Russians, Belarusians and Ukrainians in the more recent past.